What are the discursive resources surrounding "beer goggles" and their implications within the South African university context? - Stuart, Michael Jason (Rhodes University, Faculty of Humanities, Department of Psychology, 2017)
Exploring student drinking, this research provides an in-depth investigation into how "beer goggles" is constructed discursively and what implications that has within the South African university context. In doing so, research attempted to: 1) map out the discursive resources operating in the empirical research literature, public domain texts and individual talk; 2) identify the subject positions and action orientation of these constructions, and 3) to establish what gendered subjectivities are reproduced within that framework. With a qualitative and social constructionist background, this study utilised a Foucauldian discourse analytic method that included ideas from discursive research. Data collection involved five mainstream videos, three focus groups and three interviews. Along with the research literature, the videos represented the wider social constructions around "beer goggles" that are played out in the micro contexts displayed by the latter participant material. Based on their popularity on YouTube, consideration was given to videos that were the most relevant and theoretically interesting to the research project. The focus groups and interviews involved current, full time, male and female, Rhodes University students over the age of 18. Analysis revealed a common sense construction of the phenomenon that has various discursive implications. While embarrassing and sometimes out of control; "beer goggles" is constructed as a socially profitable altered state of mind that is deemed a normal and heterosexual experience in the university drinking culture. Highlighting the importance of a discursive investigation, this study provided new and alternative information that can assist further research and shed light on the debates surrounding the phenomenon. Additional research is recommended.
Keywords: Uncatalogued